The role of the Tei index in assessing for cardiotoxicity from anthracycline chemotherapy: a systematic review. Issue 1 (7th May 2021) - Bennett, Sadie; Cubukcu, Arzu; Wong, Chun Wai; Griffith, Timothy; Oxley, Cheryl; Barker, Diane; Duckett, Simon; Satchithananda, Duwarakan; Patwala, Ashish; Heatlie, Grant; Kwok, Chun Shing
Abstract : Background: Anthracycline agents are known to be effective in treating tumors and hematological malignancies. Although these agents improve survival, their use is associated with cardiotoxic effects, which most commonly manifests as left ventricular systolic dysfunction (LVSD). As such, guidelines recommend the periodic assessment of left ventricular ejection fraction (LVEF). However, as diastolic dysfunction likely proceeds systolic impairment in this setting, the role of Tei index may offer additional benefit in detecting subclinical LVSD. Methods: We conducted a systematic review to investigate the evidence for the use of Tei index in assessing subclinical cardiotoxicity in patients receiving anticancer agents. A search of Medline and EMBASE was performed and relevant studies were reviewed and narratively synthesized. Results: A total of 13 studies were included with a total of 800 patients (mean age range 46–62 years, percentage of male participants ranged from 0–86.9%). An increase in Tei index was observed in 11 studies, which suggested a decline in cardiac function following chemotherapy. Out of these, six studies indicated that the Tei index is a useful parameter in predicting cardiotoxic LVSD. Furthermore, five studies indicated Tei index to be superior to LVEF in detecting subclinical cardiotoxicity. Conclusions: Though there are some studies that suggest that Tei index may be a useful indicator in assessing subclinical anthracycline-related cardiotoxicity, the findings are inconsistent and so more studies are needed before the evaluation of Tei index is performed routinely in patients receiving chemotherapy.